Automated People Movers and Automated Transit Systems 2018 : moving to the future, building on the past : proceedings of the 16th International Conference on Automated People Movers and Automated Transit Systems, April 29-May 2, 2018, Tampa, Florida - Sproule, William J., 1948- (Online access: American Society of Civil Engineers (ASCE) American Society of Civil Engineers (ASCE) Conference Proceedings., 2018)
This collection contains 22 peer-reviewed papers on the current state and future of APMs and ATSs presented at the 16thInternational Conference on Automated People Movers and Automated Transit Systems, held in Tampa, Florida, April 29-May 2, 2018.